The Impact of Postoperative Atrial Fibrillation and Race on Long‐Term Survival after Coronary Artery Bypass Grafting. Issue 5 (2nd August 2013) - O'Neal, Wesley T.; Efird, Jimmy T.; Davies, Stephen W.; O'Neal, Jason B.; Anderson, Curtis A.; Ferguson, T. Bruce; Chitwood, W. Randolph; Kypson, Alan P.
Abstract Background and Aim Postoperative atrial fibrillation (POAF) is a known predictor of in‐hospital morbidity and short‐term survival after coronary artery bypass grafting (CABG). The impact of race and long‐term survival has not been examined in this population. We aimed to examine the influence of these factors on long‐term survival in patients undergoing CABG. Methods Patients undergoing first‐time, isolated CABG between 1992 and 2011 were included in this study. Long‐term survival was compared in patients with and without POAF and stratified by race. Hazard ratios (HR) and 95% confidence intervals (CI) were computed using a Cox regression model. Results A total of 2, 907 (22%) patients developed POAF (black n = 370; white n = 2, 537) following CABG (N = 13, 165). Median follow‐up for study participants was 8.2 years. Long‐term survival after CABG differed by POAF status and race (no POAF: HR = 1.0; white POAF: adjusted HR = 1.1, 95% CI = 1.06–1.2; black POAF: adjusted HR = 1.4, 95% CI = 1.2–1.6; pTrend = 0.0002). Black POAF patients also died sooner after surgery than their white counterparts (adjusted HR = 1.2, 95% CI = 1.02–1.4). Conclusion Black race was a statistically significant predictor of decreased survival among POAF patients after CABG. This finding provides useful outcome information for surgeons and their patients. doi: 10.1111/jocs.12178 (J Card Surg 2013;28:484–491)